'Newness to the firm'-variables in the NPD process of technology companies. (1st January 2011) - Haverila, Matti
The factors affecting the success of new products in successful and unsuccessful NPD projects have been under review by many researchers. Do the managerial conceptualisations and perceptions vary regarding the so-called newness variables between successful and unsuccessful NPD projects in the technology companies? This question has not been tackled in the prior research. This research tries to deal with this deficiency. The findings indicate that there is equivalence in how managers conceptualise the newness variables in successful and unsuccessful NPD projects. Newness is not however, a unidimensional construct in Finnish technology companies as it has been claimed in the prior research. There appears to be differences in the managerial perceptions regarding newness variables in successful and unsuccessful NPD projects. Also, some newness variables appear to have an impact on the outcome of the successful NPD project, but there are none in the unsuccessful NPD projects. The limitations and future research directions are also discussed.